Four Early Pamphlets - Godwin, William, 1756-1836 (Salt Lake City, UT : Project Gutenberg, 2004)
"Four Early Pamphlets" by William Godwin is a political collection written in the late 18th century. This compilation includes Godwin's defenses and discussions on contemporary political parties and figures, notably engaging with the Rockingham party's coalition with Lord North. Godwin's writings reflect the tumultuous political landscape of his time, particularly as Britain grappled with the repercussions of the American Revolutionary War and its internal political dynamics. The opening of the pamphlets presents a defense of the Rockingham party's coalition with Lord North, addressing criticisms regarding their integrity and motives. Godwin begins by discussing the historical significance of the period, highlighting the challenges faced by political leaders amid widespread disillusionment with the state of governance. He aims to counter the prevailing doubts about the Rockingham party's actions by presenting reasoned arguments about their necessity in serving the country's needs during a crisis. This initial exposition sets the tone for a thorough examination of political integrity, virtue, and the nature of governance, revealing Godwin's commitment to rational discourse in the face of political chaos. (This is an automatically generated summary.)
A defense of the Rockingham party, in their late coalition with the right honorable Frederic Lord North -- Instructions to a statesman, humbly inscribed to the right honourable George Earl Temple -- An account of the seminary that will be opened on Monday the fourth day of August, at Epsom in Surrey, for the instruction of twelve pupils in the Greek, Latin, French, and English languages -- The herald of literature; or, a review of the most considerable publications that will be made in the course of the ensuing winter: with extracts.
Release date is 2004-01-01
Produced by Jonathan Ingram, Amy Overmyer and PG Distributed Proofreaders
Keywords: Pamphlets